Implementation of Public Policy in Improving the Quality of Public Services in Indonesia: A Systematic Literature Review - Prima Yuana Sofwan (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The study purpose was. This study aims to analyse the implementation of public policy in improving the quality of public services in Indonesia through a systematic literature review approach. The main focus of this study is to identify the factors that influence the effectiveness of policy implementation and its impact on the quality of public services. Materials and methods. The research method used was a systematic literature review with a descriptive qualitative approach. Data sources were obtained from scientific articles indexed in Scopus, ScienceDirect, Emerald Insight, and SINTA-accredited national journals for the period 2015–2025. The analysis was conducted thematically on 30 selected articles relevant to the issues of public policy implementation and service reform. Results. The results of the study show that the success of public policy implementation in improving the quality of public services is determined by four main factors. First, the clarity and consistency of policies are the foundation for effective implementation in the field. Second, the capacity and competence of the implementing apparatus greatly influence the bureaucracy's ability to translate policies into concrete actions. Third, inter-agency coordination and public communication play an important role in maintaining synergy and increasing public trust in the government. Fourth, digital innovation and bureaucratic reform are catalysts for improving the efficiency, transparency, and responsiveness of public services. Conclusions. This study confirms that improving the quality of public services requires not only good policies, but also consistent, coordinated implementation that is adaptive to social change and technological developments.